Expression Analysis of Heavy-Chain-Only Antibodies in Cloudy Catshark and Japanese Bullhead Shark - Reo Uemura; Susumu Tanimura; Nao Yamaguchi; Ryuichi Kuroiwa; Gabriel Takashi Andrés Tsutsumi; Toshiaki Fujikawa; Kiyoshi Soyano; Kohsuke Takeda; Yoshimasa Tanaka (Marine Drugs)
Heavy chain-only antibodies in sharks are called immunoglobulin new antigen receptors (IgNAR), consisting of one variable region (VNAR) and five constant regions (C1-C5). The variable region of IgNAR can be expressed as a monomer composed of a single domain, which has antigen specificity and is thus gaining attention as a next-generation antibody drug modality. In this study, we analyzed IgNAR of the cloudy catshark and Japanese bullhead shark, small demersal sharks available in the coastal waters of Japan. By analyzing the IgNAR gene sequence and comparing it with the constant regions of five other known shark species, high homology was observed in the C4 region. Consequently, we expressed the recombinant protein of the C4 domain from the cloudy catshark in E. coli, immunized rats, and produced antibodies. The obtained antiserum and mAbs recognized the C4 recombinant protein of the cloudy catshark, but reacted minimally with the plasma of non-immunized cloudy catsharks and instead reacted with the plasma of Japanese bullhead sharks. The results of this study imply that the protein expression levels of IgNAR in cloudy catsharks may be relatively lower compared to those in Japanese bullhead sharks, however, this interpretation remains to be determined through further studies.